Mechanisms underlying methotrexate-induced pulmonary toxicity - Kim, Youn-Jung; Song, Mee; Ryu, Jae-Chun (TAYLOR & FRANCIS LTD, 2009)
Background: Methotrexate (MTX) has been widely used for the treatment of inflammatory diseases and rheumatoid arthritis, as well as a variety of tumors. However, MTX-induced pulmonary toxicity is a serious and unpredictable side effect of the therapy, which includes allergic, cytotoxic or immunologic reactions, and is a major clinical problem. Objective: To summarize the mechanisms of action involved in MTX-induced pulmonary toxicity. Methods: We reviewed the literature describing MTX-induced adverse pulmonary effects and the mechanisms of action underlying MTX-induced pulmonary toxicity. Conclusion: The mechanisms underlying MTX toxicity are complex. The clinical effects may be attributable to both the anti-inflammatory and immunosuppressive effects of MTX The mechanisms causing the side effects of MTX include mutation of the genotype, inhibition of transport, MTX-polyglutamates and P-glycoprotein binding with MTX The p38 MAPK-signaling pathway is especially associated with a pulmonary inflammatory response. These mechanisms can be applied to optimize drug treatment.
Keywords: ACTIVATED PROTEIN-KINASE; LOW-DOSE METHOTREXATE; INTERSTITIAL LUNG-DISEASES; BLOOD MONONUCLEAR-CELLS; RHEUMATOID-ARTHRITIS; GENE-EXPRESSION; ALVEOLAR MACROPHAGES; INDUCED PNEUMONITIS; EPITHELIAL-CELLS; HYPERSENSITIVITY PNEUMONITIS